Adaptive response of Lactobacillus sakei 23K during growth in the presence of meat extracts: A proteomic approach - Fadda, Silvina G. (2010)
Lactobacillus sakei is a lactic acid bacterium mainly found in meat and meat products. In order to understand the factors favoring its adaptation to meat matrix, growth parameters and survival of the strain L. sakei 23K in the presence of sarcoplasmic or myofibrillar extracts were assessed. Cytosolic proteins putatively involved in the response of this strain to meat proteins were determined using 2D electrophoresis and the significantly regulated proteins were identified by Maldi Tof-MS analyses. From the 31 differentially expressed spots, 16 occurred in the presence of myofibrillar extract while 6 proteins were modulated by the sarcoplasmic extract. Two dipeptidases were overexpressed in the presence of sarcoplasmic proteins, in correlation to the protein degradation patterns obtained by SDS-PAGE. In the presence of the myofibrillar extract, L. sakei 23K overexpressed proteins related to energy and pyrimidine metabolism as well as ala- and tyr-tRNA synthetases, involved in translation, while others corresponding to general stress response, pyrimidine, vitamin and cofactor biosynthesis were down-regulated. The supplementary nutrients furnished by meat extracts modulated the overexpression of proteins related to translation, peptide/amino acid metabolism and energy production while the stress proteins were under regulated. The results obtained here suggest that meat proteins would not represent a stress environment per se for L. sakei 23K in contrast to the harsh conditions during meat processing. This study has extended the understanding of the molecular responses and growth mechanisms of L. sakei 23K in the presence of meat proteins. The transference of genomic information into useful biological insight is an important step for the selection of well-adapted strains for the achievement of high-quality fermented products.